Building Public Trust Through Government Communication Strategies: A Case Study Of Tapera Policies In Indonesia - Sastrawan, Abim; Rahmawati, Dian Eka (Universitas Riau Kepulauan, 2025)
Government communication plays a strategic role in building public trust and ensuring policy legitimacy. This study aims to analyze the effectiveness of the Indonesian government's communication strategy in implementing the Public Housing Savings (TAPERA) policy. This study uses a qualitative approach with a case study method, utilizing secondary data sourced from official government documents, online media reports, public responses on social media, and academic literature. Data analysis was carried out using the Miles and Huberman interactive model, including the stages of data collection, reduction, presentation, and drawing conclusions. Three main indicators are used to evaluate communication strategies: information transparency, public engagement, and government responsiveness, which were developed from symmetrical two-way communication theory and public trust theory. The results show that only transparency indicators are partially effective, while public engagement and responsiveness show significant weaknesses, especially in the lack of participatory space and delayed response to public aspirations. Theoretically, this study confirms the relevance of participatory communication approaches in the context of social policies. In practical terms, this study recommends a more inclusive, adaptive, and dialogical communication strategy to increase public participation and reduce resistance to state policies.